KORELASI PERILAKU MEROKOK DAN ASPEK LINGKUNGAN TERHADAP KERJADIAN ISPA BALITA - Situmeang, Lamria; Pudyastuti, Rita Rena; Sari, Andi Nur Indah; Werdini, Yoessy Etna (Ensiklopedia of Journal, 2025)
Abstract: Acute Respiratory Infections (ARI) are one of the leading causes of morbidity and mortality from infectious diseases worldwide. Toddlers, as one of the most vulnerable groups to ARI, have a higher risk compared to other age groups. Based on a preliminary survey, Puskesmas Sentosa Baru, located in Medan Perjuangan Sub-district, Medan City, is one of the Puskesmas that often handles cases of Acute Respiratory Infection (ARI), which always ranks first in the list of the ten biggest diseases found at the Puskesmas. The purpose of the study was to determine the correlation of smoking behavior and environmental aspects to the occurrence of ARI in children under five years old. The research design used in this study was cross sectional. The research was conducted at Sentosa Baru Health Center. The research was conducted in June 2024. The population in this study were all people who had toddlers aged 0-5 years as patients at the Sentosa Baru Health Center in Medan City as many as 2685 toddlers. The sample amounted to 93 respondents. The sampling technique used in this study was the Stratified Random Sampling Technique. Data analysis was done univariate and bivariate. The results showed a relationship between smoking behavior (p value: 0.000) and the availability of ventilation (p value: 0.031). It is recommended that in an effort to prevent ARI disease in toddlers, it is hoped that the community will pay attention to the behavior of family members who smoke and the physical condition of the house by improving the condition of home ventilation that meets the requirements.Keywords: Toddlers, Smoking Behavior, Vantilation